The role of dendritic cells in tertiary lymphoid structures: implications in cancer and autoimmune diseases - Reste, Mariana; Ajazi, Kristi; Sayi-Yazgan, Ayca; Jankovic, Radmila; Bufan, Biljana; Brandau, Sven; Bækkevold, Espen S.; Petitprez, Florent; Lindstedt, Malin; Adema, Gosse J.; Almeida, Catarina R. (Frontiers in Immunology, 2024)
Tertiary Lymphoid Structures (TLS) are organized aggregates of immune cells such as T cells, B cells, and Dendritic Cells (DCs), as well as fibroblasts, formed postnatally in response to signals from cytokines and chemokines. Central to the function of TLS are DCs, professional antigen-presenting cells (APCs) that coordinate the adaptive immune response, and which can be classified into different subsets, with specific functions, and markers. In this article, we review current data on the contribution of different DC subsets to TLS function in cancer and autoimmunity, two opposite sides of the immune response. Different DC subsets can be found in different tumor types, correlating with cancer prognosis. Moreover, DCs are also present in TLS found in autoimmune and inflammatory conditions, contributing to disease development. Broadly, the presence of DCs in TLS appears to be associated with favorable clinical outcomes in cancer while in autoimmune pathologies these cells are associated with unfavorable prognosis. Therefore, it is important to analyze the complex functions of DCs within TLS in order to enhance our fundamental understanding of immune regulation but also as a possible route to create innovative clinical interventions designed for the specific needs of patients with diverse pathological diseases.